TRACKING SYSTEM USING GPS AND SMART CARD AUTHENTIFICATION BASED ON ESP 32 MCU - Suryowinoto, Andy; Herlambang, Teguh; Widjanarko, Angga Adhitya; Prabowo, Yuliyanto Agung; Tomasouw, Berny Pebo (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Logistics distribution is a series of activities that are interconnected in each process. Therefore, an information system is necessary to record, report conditions, and display the current location of items directly. An Android-based application system is vulnerable to spoofing, such as fake GPS. The application is used to falsify the coordinates of digital map locations. This research aims to develop a common tracking system and prevent Fake GPS by employing the System Development Life Cycle method, consisting of several stages, i.e., planning, analysis, design, implementation, testing, and maintenance. In this research, a prototype of the tracker tool and its information system were made. It used an RFID Smart Card for courier identity authentication and a GPS module to track position information on a digital map. RFID and GPS were controlled using the ESP32. Furthermore, the Website served as an information system to read and create a QR Code to identify the goods carried. It received data from the RFID Smart Card and GPS, stored it in the Database, and displayed it online. The test results indicated that the tracker prototype succeeded in sending location data throughout the test and gained an average distance of 6.82 meters, which was different from a commercial GPS device. It had a delay of 268.5 seconds when the location was first read. The tracker prototype had an average power consumption of 1.5 watts, an average battery life of 2 hours, 28 minutes, and 40 seconds, as well as an average battery deficiency of 36.79%. In conclusion, the system test was successful.